Stylistics of Moral Resilience: Recontextualizing Oral Poetry for Youth Character Education in Aceh Society - Monica Monalisa Hutabarat; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
This study addresses the destabilization of moral frameworks among youth in contemporary Islamic societies, a phenomenon accelerated by rapid digitization. We investigate how the structural and stylistic mechanisms of traditional oral poetry can serve as pedagogical instruments to build ethical resilience among Gen Z and millennial cohorts in modern Aceh. Methodologically, the inquiry adopts a qualitative descriptive design grounded in pedagogical stylistics to conduct a close textual analysis of twenty purposively sampled advice quatrains from the Bunga Rampai Maluku Kie Raha anthology. Our analytical framework evaluates these texts across specific operational metrics: phonology, syntax, and conceptual metaphor. The empirical results reveal that the rigid structural blueprint of the quatrain, particularly the architectural division between the foreshadowing lines (sampiran) and the semantic core (isi), functions as an efficient cognitive delivery system that optimizes mnemonic retention. Additionally, the deliberate deployment of high-impact lexical markers combined with abrupt interrogative rhetorical shifts elevates generic ethical advice into absolute behavioral boundaries. These boundaries directly reinforce Acehnese socio-legal norms. Consequently, curriculum designers and language educators in Aceh can leverage trans-regional oral literatures to diversify character education frameworks, offering a vital alternative as localized oral traditions fade from daily usage. Ultimately, this research demonstrates that UNESCO-recognized traditional poetic structures operate not merely as historical artifacts, but as dynamic socio-pedagogical interventions capable of maintaining ethical stability during acute cultural transitions.